Bilateral multisegmental zosteriform leiomyoma cutis: A rare entity - Debabrata Bandyopadhyay; Abanti Saha; Sabari Bhattacharya (Wolters Kluwer Medknow Publications, 2015)
Cutaneous leiomyomas are benign tumors derived from the smooth muscles of the skin. They are firm, skin-colored to brownish, frequently painful papules and nodules presenting either as a solitary tumor or multiple clustered lesions. Uncommon patterns of multiple leiomyoma cutis include linear, zosteriform, or dermatomal-like arrangement of lesions. We saw a 32-year-old man who presented with clusters of skin colored to reddish brown, occasionally painful papules and nodules distributed segmentally over C6 to T8 dermatomes on left side and T11 to L1 dermatomes on right side. Histopathology confirmed the diagnosis of cutaneous leiomyoma. The case is reported here for the occurrence of this benign cutaneous neoplasm in an extremely rare bilateral multisegmental distribution.